Design, modelling, and implementation of a modified double‐switch flyback‐forward converter for low power applications. Issue 4 (1st April 2019) - Eshkevari, Alireza Lahooti; Mosallanejad, Ali; Sepasian, Mohammadsadegh
Abstract : This study proposes a modified double‐switch flyback‐forward (DSFF) converter for low‐power applications with a reduced number of windings in its transformer. This circuit has resulted from the combination of the two‐switch flyback and two‐switch forward converters. It includes a simple transformer with one set of secondary side windings, and it is not necessary to design two separate sets of windings for the desired output voltage which is the main problem of other flyback‐forward converters. An auxiliary winding has been designed for self‐biasing, and consequently, it improves the overall efficiency in the no‐load condition. Due to the modifications on the previously presented two‐switch flyback‐forward converter, the circuit model has changed. This study, first, analyses the operation of the proposed converter in detail, then it explains a method to design this converter in continuous inductor current mode. Also, a start‐up voltage regulator circuit and a modified bootstrap gate driver will be investigated, and the DC and AC model of the converter will be presented. Experimental results validate the proposed DSFF converter. The tested circuit includes a DSFF converter, a pulse generator circuit, a start‐up voltage regulator, and a modified bootstrap gate driver.